Les exemples dans l’élaboration des démonstrations mathématiques : une approche sémantique et dialogique - Thomas Barrier (Recherches en Éducation)
This paper addresses the roles of examples when dealing with mathematical proof in higher education. I use the distinction between semantic and syntactic approaches to get a first insight. Then I focus on a specific role: the contribution of examples in proving. I put forward a reference framework, the dialogic approaches of logic, to offer model of validation which is enough comprehensive to give an account for both example use and formal utterance manipulation. The model is grounded on the concept of game. Two main findings are pointed out. The distinction between play level and strategy level helps to address the dynamic facet of proof process. Besides, the model permits to better grasp the common or specific aspects of formal manipulations and examples consideration, the specific ones being sometimes overvalued in my viewpoint.